Coordination Analysis of Environmental and Social Problems in Transportation System - Zhiwen Chen (Complexity)
This paper analyzes the characteristics of the transportation system and constructs a multidimensional urban public transportation evaluation index system from the perspective of basic network evaluation. The DEA efficiency evaluation model is constructed based on the perspective of environmental and social issues in transportation systems. Environmental and social issues in transportation systems refer to the differences in the average number of people carried and their technical indicators such as environmental pollution and energy consumption for different modes of transportation, which will also lead to different consumption of natural resources per unit of transportation capacity. The multidimensional public transportation system efficiency evaluation system for different evaluation scenarios provides useful technical ideas and implementation methods. To provide a basis for decision-making for transportation system planning, the operation management can help to further promote the research results in practice.